New Aliphatic Glycoside Constituent from the Fruits of Lycium chinense Miller - Lee, Joohyun; Chung, Ill-Min; Lim, Jung-Dae; A. Siddiqui, Nasir; Ahmad, Ateeque (Asian Journal of Chemistry, 2013)
One new compound as n-henecosanoyl-b-D-arabinofuranosyl-2'-(1®2)-b-D-arabinopyranosyl-(1®2)-2''-b-D-arabinopyranosyl (1®2)-2'''-b-D-arabinopyranoside (1), along with known n-eicosanoic acid were isolated from the fruits of Lycium chinense. The chemical structure of new compound was elucidated by 1D and 2D NMR spectroscopic techniques (COSY, HSQC, HMBC) aided by FAB-MS and IR spectra.